The Student’s Understanding and Response Towards Case Study Method in Arabic Language Research l Istijabatu wa Mafhum al-Thalabah fi Manhaj Dirasah al-Halah fi Bahts al-Lughah al-‘Arabiyyah - Ridlo, Ubaid; Kojin, Kojin; Umbar, Kisno (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2022)
In Arabic learning, case study method is substantial. It can make a major contribution in diagnosing cases or problems that occur in the learning process and offering solutions. The purpose of this research is to reveal the response and understanding of prospective Arabic language learning researchers to the case study method. This research is a mixed methods and the place of research is the field. The data of this research were the head and the secretary of the department, 6 lecturers, and 75 students of the Master program in Arabic Education at three universities, which were UIN Jakarta, UIN Malang, and UIN Tulungagung. The data were collected through observation, interviews, questionnaires, documentation, and FGD. Miles and Huberman model were used in this research. The findings of this research were the understanding and responses of Arabic language learning researchers towards the case study method. The indicators were: a) The case study method was discussed during lectures with lecturers, b) The majority of PBA Masters students are interested in the case study method, c) The majority of PBA Masters students were quite understand the case study methodology, d) The majority of PBA Masters students recommend the case study method to be studied and used as a thesis research method, e) The majority of PBA Masters students were interested in applying the case study method in their thesis research. This research contributed to strengthen and develop the learning methodology for research methodology subject and thesis proposal seminars subject.